Cardiovascular disease in kidney donors: matched cohort study. (1st March 2012) - Garg, Amit X; Meirambayeva, Aizhan; Huang, Anjie; Kim, Joseph; Prasad, G V Ramesh; Knoll, Greg; Boudville, Neil; Lok, Charmaine; McFarlane, Philip; Karpinski, Martin; Storsley, Leroy; Klarenbach, Scott; et al.
Abstract : Objective To determine whether people who donate a kidney have an increased risk of cardiovascular disease. Design Retrospective population based matched cohort study. Participants All people who were carefully selected to become a living kidney donor in the province of Ontario, Canada, between 1992 and 2009. The information in donor charts was manually reviewed and linked to provincial healthcare databases. Matched non-donors were selected from the healthiest segment of the general population. A total of 2028 donors and 20 280 matched non-donors were followed for a median of 6.5 years (maximum 17.7 years). Median age was 43 at the time of donation (interquartile range 34-50) and 50 at the time of follow-up (42-58). Main outcome measures The primary outcome was a composite of time to death or first major cardiovascular event. The secondary outcome was time to first major cardiovascular event censored for death. Results The risk of the primary outcome of death and major cardiovascular events was lower in donors than in non-donors (2.8 v 4.1 events per 1000 person years; hazard ratio 0.66, 95% confidence interval 0.48 to 0.90). The risk of major cardiovascular events censored for death was no different in donors than in non-donors (1.7 v 2.0 events per 1000 person years; 0.85, 0.57 to 1.27). Results were similar in all sensitivity analyses. Older age and lower income were associated with a higher risk of death and major cardiovascular events in both donors and non-donors when each group was analysed separately. Conclusions The risk of major cardiovascular events in donors is no higher in the first decade after kidney donation compared with a similarly healthy segment of the general population. While we will continue to follow people in this study, these interim results add to the evidence base supporting the safety of the practice among carefully selected donors.